2009
DOI: 10.2753/joa0091-3367380405
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Privacy Concerns and Preference for Degree of Regulatory Control

Abstract: Esta es la versión de autor del artículo publicado en:This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription CONSUMER PRIVACY CONCERNS AND PREFERENCE FOR DEGREE OFREGULATORYCONTROL A Study of Mobile Advertising in JapanShintaro Okazaki, Hairong Li, and Morikazu Hirose ABSTRACT: This study explores the consequences of consumers' privacy concerns in the context of mobile adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
174
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 41 publications
9
174
1
2
Order By: Relevance
“…Prior literatures revealed that consumers' ability on behavioral control has a significant positive influence on many behavioral intentions (Bauer, et al, 2005;Carroll, et al, 2007;Hongwei, et al, 2010;Leppaniemi & Karjaluoto, 2005;Merisavo, et al, 2010;NOKIA, 2002;Nysveen, et al, 2005;Sheppard, Hartwick, & Warshaw, 1988;Tripathi & Siddiqui, 2008;Tsang, et al, 2004;Venkatesh, et al, 2003). In fact, studies in developed countries disclosed that many consumers appreciate rights to have behavioral control (Hongwei, et al, 2010;Leppaniemi & Karjaluoto, 2005;Okazaki, et al, 2009). …”
Section: Review Of Literaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior literatures revealed that consumers' ability on behavioral control has a significant positive influence on many behavioral intentions (Bauer, et al, 2005;Carroll, et al, 2007;Hongwei, et al, 2010;Leppaniemi & Karjaluoto, 2005;Merisavo, et al, 2010;NOKIA, 2002;Nysveen, et al, 2005;Sheppard, Hartwick, & Warshaw, 1988;Tripathi & Siddiqui, 2008;Tsang, et al, 2004;Venkatesh, et al, 2003). In fact, studies in developed countries disclosed that many consumers appreciate rights to have behavioral control (Hongwei, et al, 2010;Leppaniemi & Karjaluoto, 2005;Okazaki, et al, 2009). …”
Section: Review Of Literaturesmentioning
confidence: 99%
“…Furthermore, consumers require fair opportunities to have control over the transaction process to boost their confidence for further business deals (Leppaniemi & Karjaluoto, 2005;Milne & Rohm, 2000;Okazaki, Li, & Hirose, 2009). Prior to that, consumers' knowledge about how to utilize mobile communication technologies together with technology facilitating conditions also found to be equally important to ensure participation in mobile advertising activities (Beneke, et al, 2010;Nysveen, et al, 2005).…”
Section: Review Of Literaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, subscribers who opted in to e-mail newsletters may be reluctant to provide their personal information because the subscription mechanism may not be perceived as a sufficient safeguard. In this context, Okazaki et al [37] examined consumers' preferences on the desired strictness of advertising regulation in mobile advertising delivered by e-mail newsletters. Their findings suggest that information privacy concerns substantially attenuate trust and strengthen the risk in mobile advertising, which in turn acts as a direct predictor of preference for regulatory strictness.…”
mentioning
confidence: 99%
“…Wang et al 2015;Quinn 2015;Liu 2015;Combe 2015;Kshetri 2014;Hahn 2014;Gaff et al 2014;Cate 2014;Bardi et al 2014;Karabey 2012) and consumer privacy with mobile environment, mobile devices (Zhang et al 2013;Okazaki et al 2009;Praher and Praher 2008;Holtmanns 2002;Buck et al 2014) All the happenings show that ''we live in an era of an explosion of data'' (Landau 2015). In light of the many studies and which is referred to above, the purpose of this study is to understand consumer privacy in the era of big data.…”
Section: Consumer Privacy In the Era Of Big Datamentioning
confidence: 99%